Barriers to E-procurement Integration in Automobile Industry: A Suppliers' perspective - Aznur Hajar, Abdullah; Ab Hamid, Noor Raihan (2008)
Most automakers find that integrating with their suppliers in an e-procurement environment able to help them streamlining information across diverse suppliers base. However, many barriers to the integration of e-procurement could hold back suppliers' from realising the integration with automakers (buyers). This study deals with e-procurement integration (EI) barriers within the Malaysian automobile industry, focusing on parts and components suppliers as the target respondents. A number of barriers, grouped as buyers, financial, IT and security barriers have been identified to influence suppliers' decision to participate in EI network. However, only buyers' barriers were identified as the major impediments to EI within the industry. Overall, the suppliers who take on passive approach to EI view buyers' barrier as significant.